A high-efficiency piezoelectric-based integrated power supply for low-power platforms. (August 2020) - Hassan, Alaa; El-Shaboury, Aya; Mohamed, Karim; Askar, Mohamed; Mowafy, Osama; Mosaad, Yasmine; Hassan, Ali H.; Mostafa, Hassan
Abstract: In this paper, a high-efficiency piezoelectric-based integrated power supply (PEPS) is proposed. The proposed PEPS supplies low-power platforms (i.e., Passive infrared sensor) with 51.4% power conversion efficiency (PCE). The piezoelectric transducer designing and modeling are developed using COMSOL. Furthermore, a Verilog-A model is presented to be integrated with the proposed power management unit where the output DC supply is 3.3 V. Finally, a prototype of the proposed PEPS is implemented using UMC 0.13 μm CMOS technology, the design occupies approximately 0.092 mm 2 .